Experimental investigation on mechanisms of fine particles generation for the Borealis Borstar multistage olefin polymerization process. Issue 36 (30th April 2018) - Jiang, Binbo; Ye, Jian; Liao, Zuwei; Shi, Xiaomei; Huang, Zhengliang; Wang, Jingdai; Yang, Yongrong
ABSTRACT: Simultaneous production of large amount of undesired fine particles is a big trouble in the Borstar multistage olefin polymerization process. Aiming at reducing the fine particles, the formation mechanism and formation location of the fine particles were thus studied. First, the influence of catalyst nature was considered. Second, the ash content, bulk density, morphology, and molecular weight distribution of polyethylene with different particle sizes from the small‐scale loop prepolymerization reactor, supercritical loop reactor, and gas phase fluidized bed reactor were studied, respectively. In combination with particle growth model, scanning electron microscope, gel permeation chromatography, and laser particle size analyzer, the particle morphology and growth kinetics were investigated. The results showed that fine particles were mostly generated in the supercritical loop reactor, and were significantly affected by the particle size distribution, residence time distribution, and particle fragmentation of the catalyst. Furthermore, scanning electron microscope images showed the catalysts with low activity tended to generate more fine particles. Based on these results, several strategies for reducing the amount of fine particles were proposed, which could be applied in the industrial process. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46589. Abstract :